Proceedings of the 5th ACM International Symposium on Mobile Ad Hoc Networking and Computing 2004
DOI: 10.1145/989459.989477
|View full text |Cite
|
Sign up to set email alerts
|

Capacity bounds for three classes of wireless networks

Abstract: We present capacity results for three classes of wireless ad hoc networks, using a general framework that allows their unified treatment. The results hold with probability going to 1 as the number of nodes in the network approaches infinity, and under a general model for channel fading.We first study asymmetric networks that consist of n source nodes and around n d destination nodes, communicating over a wireless channel. Each source node creates data traffic that is directed to a destination node chosen at ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 16 publications
2
91
0
Order By: Relevance
“…It is shown that with n ad-hoc nodes and m base stations, the benefits provided due to the base stations are insignificant when m grows asymptotically slower than √ n. In [8], in a similar network setting, it is shown that Θ(1) per node throughput can be achieved when the nodes can optimally control their transmission powers. In [9], it is shown that a hybrid network with n wireless nodes and n d access points, inter-connected by wires, can achieve throughput gains only when 1 2 < d < 1. Unlike our work, the above efforts assume that the traffic flows are established between randomly chosen ad-hoc nodes and the base stations or access points are for relaying purposes only.…”
Section: Our Results In Briefmentioning
confidence: 99%
See 1 more Smart Citation
“…It is shown that with n ad-hoc nodes and m base stations, the benefits provided due to the base stations are insignificant when m grows asymptotically slower than √ n. In [8], in a similar network setting, it is shown that Θ(1) per node throughput can be achieved when the nodes can optimally control their transmission powers. In [9], it is shown that a hybrid network with n wireless nodes and n d access points, inter-connected by wires, can achieve throughput gains only when 1 2 < d < 1. Unlike our work, the above efforts assume that the traffic flows are established between randomly chosen ad-hoc nodes and the base stations or access points are for relaying purposes only.…”
Section: Our Results In Briefmentioning
confidence: 99%
“…While there has been a surge in interest in modelling various kinds of hybrid networks (to be elaborated in section II) [3], [4], [5], [2], [6], [1], [7], [8], [9], [10], [11], the above question has not been answered to date. While the use of shorter range and hence, higher rate wireless ad-hoc links may improve spatial reuse (more simultaneous transmissions can occur) [12], the use of multi-hop relaying increases the number of wireless hops traversed and this reduces the achievable throughput.…”
Section: Introductionmentioning
confidence: 99%
“…Following this work, extensive studies have been conducted to achieve a tighter capacity bound [2][3][4][5][6][7][8]. Franceschetti et al [2] apply percolation theory to obtain a per-node transmission rate higher than 1 ( ) n !…”
Section: W N N !mentioning
confidence: 99%
“…A capacity of 1 √ n per node is verified through extensive simulations. The effect of channel fading is considered in [2], [3] and [4]. Another branch of work focuses on different traffic patterns in wireless networks.…”
Section: B Related Workmentioning
confidence: 99%
“…Following the work, researchers have studied capacity scaling laws under different assumptions or applications, e.g. in [2] [3][4] [6][8] [15] [16].…”
Section: Introductionmentioning
confidence: 99%